Sensors and instrumentation. Volume 5 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 - Wee Sit, Evro; Walber, Chad; Walter, Patrick; Seidlitz, Steve (Springer, 2017)
Sensors and Instrumentation, Volume 5. Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the fifth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Sensors and Instrumentation, including papers on: Sensor Applications Accelerometer Design Accelerometer Calibration Sensor Technology.
International conference proceedings.
Keywords: Modal analysis -- Congresses.; Structural dynamics -- Congresses.; Engineering instruments -- Congresses.; elektronické knihy; electronic books